BAHAN PENGENTAL YOGURT DARI EKSTRAK KULIT KAYU BALAKKA (Phyllantus emblica) - Melvariani Syari Batubara; Nur Melina Nasution; Dea Amanda Siregar; Sutan Muda; Ilmi Aulina Rahim (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2025)
This research explores the use of Balakka Bark as a natural thickening agent in making yoghurt. Balakka (Phyllanthus emblica) is one of the local wisdom plants of Southern Tapanuli. The research was carried out at the Biology Laboratory of the Universitas Muhammadiyah Tapanuli Selatan, the Plant Systematics Laboratory of the Medanense Herbarium (MEDA) of the Universitas Sumatera Utara and the Organic Chemistry/Chemical Process Laboratory of the FMIPA University Sumatera Utara from March to July 2024. This research aims to identify the chemical content of the Balakka Plant and evaluate the process making yoghurt with Balakka Bark Extract. The method used includes making a water extract from Balakka Bark and testing its chemical content, such as terpenoids, flavonoids, tannins and polyphenols. The results show that Balakka Bark Extract can improve the quality of yoghurt, with organoleptic tests showing the optimal ratio between yoghurt and Balakka Bark Extract is 1 : 1 (Y1B1). The tannin and polyphenol content in Balakka Bark Extract influences the viscosity of yoghurt, because both contain phenolic acids, where phenolic acids function as coagulant enzyme activities. This research highlights the potential economic and health benefits of using Balakka in the food industry, as well as providing education to the public about this natural ingredient.